KEEFEKTIFAN CHILD-CENTERED PLAY THERAPY (CCPT) UNTUK MENINGKATKAN KETERAMPILAN SOSIOEMOSIONAL SISWA SEKOLAH DASAR - Miranti Widi Andriani (Nurul Jadid University, 2018)
The purpose of this study was to improve the socio-emotional skills of elementary school students through the Child-Centered Play Therapy (CCPT) approach through three procedures, namely the development of new, more adaptive thoughts and behaviors, guiding students to utilize problem-solving strategies by playing and telling stories, and provide concrete examples with abstract ideas and emotions by learning new skills. This type of research is experimental research with Single Subject Design. The subjects of this study were 3 students at Bangkalan Martajasah Elementary School who had a low level of socio-emotional skills. The results showed that there was an increase in socio-emotional skills before-after getting a CCPT intervention. The conclusion that can be drawn from the study is that the CCPT intervention is effective in improving socio-emotional skills both individually and in groups. Suggestions from this study are that supervising teachers can use the CCPT approach as a preventive and curative effort for students who have low socio-emotional skills. For further research, it should be followed up using pure experiments using a control group.